PCR- and restriction endonuclease-based detection of IDH1 mutations - Meyer, Jochen; Pusch, Stefan; Balß, Jörg; Capper, David; Müller, Wolf C.; Christians, Arne; Hartmann, Christian; Deimling, Andreas von (Brain pathology, 2010)
Hotspot mutations in codon 132 of the gene encoding isocitrate dehydrogenase 1 (IDH1) have emerged as the most frequent DNA alteration in astrocytomas, oligodendrogliomas and oligoastrocytomas. These mutations have been shown to be of significant diagnostic and prognostic value. So far, assessment of IDH1 mutation relied on DNA sequencing techniques. We generated a set of primers suitable for endonuclease-based detection of hotspot mutations in codon 132 of IDH1. This primer set will allow determining these mutations without the need of DNA sequencing. One set of primer sets is designed to detect the presence or absence of IDH1 mutations in codon 132, while the other primer sets individually recognize the R132H, R132C, R132S, R132G and R132L mutations.